فاعلية توظيف التعليم الإلكتروني في توفير بيئة تعليمية تفاعلية تخدم القضايا التعليمية - المنتصر, حكيم خليفة (Al-Qurtas, 2026)
فاعلية توظيف التعليم الإلكتروني في توفير بيئة تعليمية تفاعلية تخدم القضايا التعليمية